ECONOMIC EFFICIENCY ASSESSMENT OF DEPOSITS WITH DIMINISHING GAS PRODUCTION - A. E. Suleymankadieva; T. A. Lukyanchikova (Дискурс, 2018)
The article considers opportunities of increasing the efficiency of fields with diminishing gas production on the basis of enterprise activity system analysis using a dynamic normal based on system characteristics matrix. In this study, system characteristics matrix is used as the leading methodological approach. It was developed and proposed by the famous scientist I. M. Syroyozhin, and presents an information model of a system of indicators characterizing the production, financial, economic and managerial activities of an enterprise. It provides a comprehensive idea of the financial and economic state of the enterprise by using quantitative, qualitative and spatial-temporal components. The methodical approach was adopted and tested on the example of evaluating the efficiency of Medvezhinsky gas production directorate, the results of which allowed to make recommendations as to how to enhance the economic efficiency of gas producing enterprises.